2021
DOI: 10.2147/copd.s286360
|View full text |Cite
|
Sign up to set email alerts
|

Combined Pulmonary Fibrosis and Emphysema (CPFE) Clinical Features and Management

Abstract: Background Combined pulmonary fibrosis and emphysema (CPFE) is an underrecognized syndrome characterized by chronic, progressive disease with a dismal prognosis. Frequent co-morbidities with a higher incidence than in idiopathic pulmonary fibrosis or emphysema alone are pulmonary hypertension (WHO group 3) in 47–90% of the patients and lung cancer in 46.8% of the patients. Objective Review current evidence and knowledge concerning diagnosis, risk factors, disease evolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 48 publications
1
36
0
Order By: Relevance
“…Regarding clinical and demographic variables of patients' groups and control subjects, we observed that the CPFE patients are the group that presents the lowest DL CO , FEV 1 , and FVC values when were compared with the IPF patients and the PAC subjects. Interestingly, despite the decrease in FEV 1 and FVC, the FEV 1 /FVC ratio was maintained at >70%, another characteristic previously reported in CPFE patients (9,13,25).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Regarding clinical and demographic variables of patients' groups and control subjects, we observed that the CPFE patients are the group that presents the lowest DL CO , FEV 1 , and FVC values when were compared with the IPF patients and the PAC subjects. Interestingly, despite the decrease in FEV 1 and FVC, the FEV 1 /FVC ratio was maintained at >70%, another characteristic previously reported in CPFE patients (9,13,25).…”
Section: Discussionsupporting
confidence: 55%
“…The CPFE is a recently described entity in which emphysema is predominantly in the upper and fibrosis in the basal lung lobes and subpleural regions ( 9 , 12 ). The etiology and pathogenesis of this disease remain unknown and result in a diagnostic challenge with poor prognosis and high mortality ( 4 , 12 , 13 ). In 2020, Kinjo et al reported that the minor allele of the AGER rs2070600 was associated with CPFE related with COPD patients in the dominant model in a Japanese cohort ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…CPFE is usually not included in the ILAs; we propose its inclusion here to avoid a separate section. CPFE is a syndrome occurring in smokers or ex-smokers characterized by dyspnea that is often severe, with relatively preserved lung volumes, severely impaired gas exchange, and an increased risk of pulmonary hypertension, and is associated with a very poor prognosis, including an increased risk of lung cancer [18][19][20][21]. It is also encountered in the setting of connective tissue diseases, especially rheumatoid arthritis, which has similar features to 'idiopathic' (tobacco-related) CPFE [18].…”
Section: Interstitial Lung Abnormalities and Combined Pulmonary Fibrosis And Emphysemamentioning
confidence: 99%
“…CPFE may be associated with a higher risk of pulmonary hypertension and death (although this is controversial) [22]. Despite the publication of several papers since the first description by Wiggins et al [21], the pathophysiology and mechanisms of CPFE largely remain obscure [18,20].…”
Section: Interstitial Lung Abnormalities and Combined Pulmonary Fibrosis And Emphysemamentioning
confidence: 99%
See 1 more Smart Citation